Case report: Gait-induced palilalia in a patient with hemiplegia due to cerebral infarction - Kaneko, Yoshiyuki; Suzuki, Takahiro; Nakajima, Hideto; Kanamori, Tadashi; Suzuki, Masahiro (Frontiers in Human Neuroscience, 2024)
Background: Palilalia is a type of speech characterized by compulsive repetition of words, phrases, or syllables. Several reports have noted that palilalia can occur in response to external verbal stimuli. Here we report, for the first time, a patient with palilalia induced by gait, which we called "movement-related palilalia".Case presentation: Eleven months after the onset of cerebral infarction sparing the right precentral gyrus and its adjacent subcortical regions, a 63-year-old, left-handed, Japanese man was referred for psychiatric consultation because of a complaint of irritability caused by the stress of compulsive repetition of a single meaningless word, "wai". The repetition of a word, palilalia, in this case was characterized by being observed predominantly during walking, and that it was in melodic tones. The palilalia during walking disappeared almost completely after five months of treatment with carbamazepine 600 mg.Conclusions: Palilalia induced by gait can occur in patients with a history of cerebral infarction. This palilalia during walking may be due to reorganization of networks in areas nearby or surrounding cerebral infarcts.